Pelatihan dan Pengembangan Sistem Akuntansi pada Badan Usaha Milik Negeri Rajuno Hitipori di Negeri Rutong Kota Ambon - Meidylisa Patty; Mis Fertyno Situmeang; Sally Paulina Sandanafu; Nova Angelin Kailuhu; Vanessa Acnes Christoffel; Filiyan Huwa; Marsanda Imelia Molle (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Community Service is the application of science and technology carried out at the state-owned enterprise (BUMNeg) Rajuno Hitipori in Negeri Rutong, Ambon City, as a partner fostered by Ambon State Polytechnic. The objective of this community service activity is to enhance the accounting knowledge of BUMNeg administrators and business unit managers and to provide an easy and adequate financial reporting system for BUMNeg business management.The method used is participatory action research in the form of training and mentoring for the preparation of financial reports for BUMNeg administrators and business unit managers using financial report preparation guidelines. The results achieved include BUMNeg administrators acquiring accounting knowledge and skills and being able to utilize the Excel for Accounting application provided for financial reporting.